2016
DOI: 10.1016/j.chemosphere.2016.09.063
|View full text |Cite
|
Sign up to set email alerts
|

NO2 inhalation causes tauopathy by disturbing the insulin signaling pathway

Abstract: Air pollution has been evidenced as a risk factor for neurodegenerative tauopathies. NO, a primary component of air pollution, is negatively linked to neurodegenerative disorders, but its independent and direct association with tau lesion remains to be elucidated. Considering the fact that the insulin signaling pathway can be targeted by air pollutants and regulate tau function, this study focused on the role of insulin signaling in this NO-induced tauopathy. Using a dynamic inhalation treatment, we demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Additionally, animal studies have demonstrated that direct NO 2 inhalation caused a worsening of spatial learning and memory and promoted dose-dependent Aβ deposition [78], while other studies have reported that direct NO 2 inhalations promote proinflammatory mechanisms that originate from the periphery, which then translocate to the brain [79][80][81], excitotoxically disrupting synaptic plasticity mechanisms of learning and memory such as long-term potentiation (LTP) [82]. Finally, NO 2 inhalations were shown to induce tauopathy by disturbing the insulin signaling pathway via p38 MAPK and/or JNK activation and IRS-1/AKT/GSK-3β attenuation [83]. Taken together, there is strong evidence that chronic exposure to high levels of anthropogenically released NO 2 in the atmosphere can lead to the genesis of neurocognitive symptoms as a function of ATN that may lead to ADRD.…”
Section: Nitrogen Dioxide (No2)mentioning
confidence: 99%
“…Additionally, animal studies have demonstrated that direct NO 2 inhalation caused a worsening of spatial learning and memory and promoted dose-dependent Aβ deposition [78], while other studies have reported that direct NO 2 inhalations promote proinflammatory mechanisms that originate from the periphery, which then translocate to the brain [79][80][81], excitotoxically disrupting synaptic plasticity mechanisms of learning and memory such as long-term potentiation (LTP) [82]. Finally, NO 2 inhalations were shown to induce tauopathy by disturbing the insulin signaling pathway via p38 MAPK and/or JNK activation and IRS-1/AKT/GSK-3β attenuation [83]. Taken together, there is strong evidence that chronic exposure to high levels of anthropogenically released NO 2 in the atmosphere can lead to the genesis of neurocognitive symptoms as a function of ATN that may lead to ADRD.…”
Section: Nitrogen Dioxide (No2)mentioning
confidence: 99%
“…The loss of E-cad expression is an important step during the EMT developmental program in human lung cancer . Our previous study showed that exposure to PM 2.5 and PM 10 resulted in an EMT activation and extracellular matrix (ECM) degradation in A549 cells . Whereas, as a dominant composition of SIA during severe haze particulate pollution in north of China, linking these effects specifically to (NH 4 ) 2 SO 4 -exposure is somewhat difficult.…”
Section: Resultsmentioning
confidence: 99%
“…9 Our previous study showed that exposure to PM 2.5 and PM 10 resulted in an EMT activation and extracellular matrix (ECM) degradation in A549 cells. 31 Whereas, as a dominant composition of SIA during severe haze particulate pollution in north of China, linking these effects specifically to (NH 4 ) 2 SO 4 -exposure is somewhat difficult. In this study, (NH 4 ) 2 SO 4 resulted in EMT phenotype marker changes, such as a reduction in E-cad and an elevation in Fn1 in both the A549 and the BEAS-2B cell lines.…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…In the present study, considering the mice were exposed to 5 h/day, the exposure concentration of NO 2 was 1.56 ppm (TWA, based on the 8 h work shift), being in the range of reported levels in some occupational exposure places. In addition, our previous studies have demonstrated that exposure to NO 2 (2.5 ppm, 5 h/day) causes cognitive abnormalities in adult mice and male offspring but does not lead to lethality. , …”
Section: Methodsmentioning
confidence: 93%
“…In addition, our previous studies have demonstrated that exposure to NO 2 (2.5 ppm, 5 h/day) causes cognitive abnormalities in adult mice and male offspring but does not lead to lethality. 28,33 Dams in NO 2 -and air-exposed groups were sacrificed at E10.5, E13.5, E15.5, and E18.5 to obtain embryos, and the placenta and fetal brain (including forebrain and hindbrain) were dissected. Each group included at least six dams, and a total of 6−8 embryos (1, 2 embryo(s) per dam) were randomly selected for further analysis.…”
Section: Mice and Nomentioning
confidence: 99%